Esterification of levulinic acid to levulinate esters in the presence of sulfated silica catalyst - Nur Aainaa Syahirah Ramli; Nur Irsalina Hisham; Nor Aishah Saidina Amin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Levulinic acid (LA) is one of biomass derived building block chemicals with various applications. Catalytic esterification of LA with alkyl alcohol produces levulinate ester which can be applied as fragrance, flavouring agents, as well as fuel additives. In this study, a series of sulfated silica (SiO2) catalyst was prepared by modification of SiO2 with sulfuric acid (H2SO4) at different concentrations; 0.5 M to 5 M H2SO4. The catalysts were characterized, and tested for esterification of LA with ethanol to ethyl levulinate (EL). The effect of various reaction parameters including reaction time, catalyst loading and molar ratio of LA to ethanol on esterification of LA to EL were inspected. The catalyst with high concentration of acid sites seemed suitable for LA esterification to EL. Among the sulfated SiO2 catalysts tested (0.5 M-SiO2, 1 M-SiO2, 3 M-SiO2 and 5 M-SiO2), 3 M-SiO2 exhibited the highest performance with the optimum EL yield of 54% for reaction conducted at reflux temperature for 4 h, 30% 3 M-SiO2 loading and LA to ethanol molar ratio of 1:20. Besides, the reusability of 3 M-SiO2 catalyst for LA esterification with ethanol was examined for five cycles. Esterification of LA with methanol and 1-butanol were also carried out for methyl levulinate (ML) and butyl levulinate (BL) productions with 69% and 40% of ML and BL yields, respectively. This study demonstrates the potential of sulfated SiO2 catalyst for levulinate ester production from LA at mild process condition.